Memantine agonist action at dopamine D2High receptors - Seeman, Philip (2008)
Memantine is reported to improve symptoms in moderate cases of Alzheimer´s disease and Parkinson´s disease, but is also known to trigger psychosis in some Parkinson patients. Because these clinical features suggested a possible dopamine component of memantine action, we measured the potency of memantine on the functional high-affinity state of dopamine D2 receptors, or D2(High). Using [(3)H]domperidone to label D2 receptors, the memantine dissociation constant at D2(High) was 917 +/- 23 nM for rat striatal D2 receptors and 137 +/- 19 nM for human cloned D2Long receptors. The memantine dissociation constant for striatal N-methyl-D-aspartate (NMDA) receptors labeled by [(3)H]MK 801 was 2200 +/- 400 nM. Memantine stimulated the incorporation of [(35)S]GTP-gamma-S into D2-expressing Chinese Hamster Ovary cells with a dissociation constant of 1200 +/- 400 nM. Memantine, between 200 and 2000 nM, directly acted on D2(High) to inhibit the release of prolactin from isolated anterior pituitary cells in culture. Because the memantine potencies at NMDA receptors and dopamine D2(High) receptors are of a similar order of magnitude, it is likely that the clinical features of memantine can be attributed to its action at both types of receptors.